In vivo cartilage strain increases following medial meniscal tear and correlates with synovial fluid matrix metalloproteinase activity. Issue 8 (1st June 2015) - Carter, Teralyn E.; Taylor, Kevin A.; Spritzer, Charles E.; Utturkar, Gangadhar M.; Taylor, Dean C.; Moorman, Claude T.; Garrett, William E.; Guilak, Farshid; McNulty, Amy L.; DeFrate, Louis E.
Abstract: Meniscal tears are common injuries, and while partial meniscectomy is a frequent treatment option, general meniscus loss is a risk factor for the development of osteoarthritis. The goal of this study was to measure the in vivo tibiofemoral cartilage contact patterns in patients with meniscus tears in relation to biomarkers of cartilage catabolism in the synovial fluid of these joints. A combination of magnetic resonance imaging and biplanar fluoroscopy was used to determine the in vivo motion and cartilage contact mechanics of the knee. Subjects with isolated medial meniscus tears were analyzed while performing a quasi-static lunge, and the contralateral uninjured knee was used as a control. Synovial fluid was collected from the injured knee and matrix metalloproteinase (MMP) activity, sulfated glycosaminoglycan, cartilage oligomeric matrix protein, prostaglandin E2, and the collagen type II cleavage biomarker C2C were measured. Contact strain in the medial compartment increased significantly in the injured knees compared to contralateral control knees. In the lateral compartment, the contact strain in the injured knee was significantly increased only at the maximum flexion angle (105°). The average cartilage strain at maximum flexion positively correlated with total MMP activity in the synovial fluid. These findings show that meniscal injury leads to loss of normal joint function and increased strain of the articular cartilage, which correlated to elevated total MMP activity in the synovial fluid. The increased strain and total MMP activity may reflect, or potentially contribute to, the early development of osteoarthritis that is observed following meniscal injury.